Crystal Structure of Apraclonidine Hydrochloride. (21st October 2013) - Hirayama, Noriaki
Abstract : Apraclonidine is used for the treatment of postsurgical elevated intraocular pressure. The crystal structure of its hydrochloride, C9 H10 Cl2 N4 · HCl, was determined by X-ray analysis. The crystal belongs to space groupP 2 1 / n with the cell dimensionsa = 9.665 ( 10 ), b = 11.8624 ( 14 ), c = 10.5675 ( 11 ) Å, andβ = 92.199 ( 9 ) °. The finalR (all reflections) value is 0.053. Apraclonidine has a more twisted structure than its related drug of clonidine. The nitrogen atom bridging the two rings is protonated.